A novel retractable stiffener-based disk-shaped active compliant polishing tool - Arunachalam, Adhithya Plato Sidharth (2022)
A novel active variable compliance polishing tool is proposed to improve the control over the area of contact and pressure distribution during polishing. This active compliance is achieved by employing a retractable stiffener-based design. This novel tool can provide a continuous range of compliance as per the polishing requirements. The design, fabrication and testing of this newly developed tool are reported. Static pressure distribution tests and material removal study are conducted for three different compliance values by changing the stiffeners positions. Appreciable changes in static contact pressure and material removal depth are observed as the stiffeners positions are changed. Further, numerical pressure distribution and load-displacement response simulated using a finite element model shows good agreement with the experimental measurements. This study paves the way for better control of polishing conditions in an automated environment.